Catecholamines Induce Left Ventricular Subclinical Systolic Dysfunction: A Speckle-Tracking Echocardiography Study - Kvasnička, Jan; Zelinka, Tomáš; Petrák, Ondřej; Rosa, Ján; Štrauch, Branislav; Krátká, Zuzana; Indra, Tomáš; Markvartová, Alice; Widimský, Jiří; Holaj, Robert (Cancers, 2019)
Background: Pheochromocytomas (PHEO) are tumors arising from chromaffin cells from the adrenal medulla, having the ability to produce, metabolize and secrete catecholamines. The overproduction of catecholamines leads by many mechanisms to the impairment in the left ventricle (LV) function, however, endocardial measurement of systolic function did not find any differences between patients with PHEO and essential hypertension (EH). The aim of the study was to investigate whether global longitudinal strain (GLS) derived from speckle-tracking echocardiography can detect catecholamine-induced subclinical impairments in systolic function. Methods: We analyzed 17 patients (10 females and seven males) with PHEO and 18 patients (nine females and nine males) with EH. The groups did not differ in age or in 24-h blood pressure values. Results: The patients with PHEO did not differ in echocardiographic parameters including LV ejection fraction compared to the EH patients (0.69 ± 0.04 vs. 0.71 ± 0.05; NS), nevertheless, in spackle-tracking analysis, the patients with PHEO displayed significantly lower GLS than the EH patients (-14.8 ± 1.5 vs. -17.8 ± 1.7; p < 0.001). Conclusions: Patients with PHEO have a lower magnitude of GLS than the patients with EH, suggesting that catecholamines induce a subclinical decline in LV systolic function.
Keywords: catecholamine; pheochromocytoma; speckle-tracking echocardiography; subclinical systolic dysfunction; global longitudinal strain